Implementasi Media Wordwall untuk Meningkatkan Keaktifan dan Kemampuan Berpikir Kreatif Siswa SMP 4 Bae Kudus - Amaliyah, Linda Nurul; Azka, Binta Atiul; Alfaris, Muh Rafi; Nur, Dany Miftah M. (Ruang Publikasi Ilmiah, 2025)
The problems faced by teachers in implementing learning are diverse, such as low student activeness and creative thinking skills. The presence of Wordwall learning media is expected to overcome both problems. The purpose of writing this article is to find out: 1) Implementation of Wordwall learning media in social studies lessons in class VIII G SMP N 4 Bae; 2) The results of increasing learning activeness and cultivation of creative thinking character of students through social studies learning by using Wordwall media at SMP N 4 Bae; 3) The driving factors and inhibitors in the implementation of Wordwall learning media in class VIII G SMP N 4 Bae. Descriptive qualitative research methods include test, observation, and interviews. The results of this study: 1) Implementation of Wordwall learning media, there are 3 stages (opening, core, closing); 2) Wordwall learning media proved to be effective in increasing students' learning activeness and critical thinking skills; 3) The driving factors are the availability of sarpras, easy access to Wordwall, and student enthusiasm. As well as inhibiting factors in the form of technical and non-technical constraints, limited learning time, and students who are arbitrary. In conclusion, the implementation of Wordwall learning media can increase the activeness and creative thinking skills of students in SMP 4 Bae Kudus